PERAN PEMIMPIN DALAM MELAKSANAKAN HUMAN RELATION UNTUK MENINGKATKAN MOTIVASI KARYAWAN LPP RRI SURAKARTA - Tri Atmadja, Oky Widhi (Transformasi, 2015)
This research is descriptive-qualitative that aim to know the role of leader in increased themotivation employees LPP RRI Surakarta.The research used analysis interactive, theresearch results show that the role of leader in LPP RRI Surakarta very suit able asemployees motivator and give a sense of responsibility so that the employees can achieve aachievement as proof of successful leadership in motivating like create relation amongemployees so the comfort able can be realized.Key Word: leadership, human relation, motivation.